THE PLACE OF NATIONAL VALUES IN MORAL AND MORAL EDUCATION - Abdinazarova Bibiaysha Erkin kizi ,Xolmuminova Oygul Jumayevna (International Journal of Literature and Language Studies, 2026)
This article analyzes the role of national values in spiritual and moral education through pedagogical, axiological and sociocultural approaches. The central thesis is that national values are not decorative elements of educational discourse, but systematic pedagogical resources that shape moral choice, social responsibility, civic position and self-awareness. The study relies on theoretical analysis, content analysis, comparative-pedagogical generalization and conceptual modeling. The results identify the educational functions of national values, the mechanisms of integrating them into the learning process and their practical application in extracurricular educational activities. The article argues that values should not remain at the level of formal slogans; they should be implemented through curricula, pedagogical communication, collective activity, family cooperation and a coherent institutional educational environment.